2015
DOI: 10.13075/mp.5893.00196
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occupational exposure to radio frequency electromagnetic fields

Abstract: StreszczenieWstęp: Dyrektywa 2013/35/UE nałożyła obowiązek implementacji przepisów UE do prawa krajowego. Celem pracy jest ocena aktualnego stanu zagrożeń wynikających ze stosowania urządzeń wytwarzających PEM RF w zakresie od 100 kHz do 300 GHz oraz wskazanie urządzeń i miejsc pracy o najwyższym ryzyku narażenia zdrowia pracowników. Materiał i metody: Materiał stanowiły dane pochodzące z badań i pomiarów PEM RF realizowanych w Pracowni Zagrożeń Elektromagnetycznych Instytutu Medycyny Pracy im. prof. J. Nofera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
1
4
0
2
Order By: Relevance
“…There is very limited data on occupational exposure to EMF at BCs. The findings of our study are consistent with other reported data from Poland [11], where the values ranging 0.4-9.6 V/m were found in workplac- es operating at VHF (87.5-108 MHz). Electromagnetic fields exposure in Polish BCs was slightly lower than that reported by Vangelova et al in the Bulgarian Broadcast Centers [5], where the equivalent time-weighted average was 2.12-3.9 V/m (vs. 0.54-2.74 V/m in this study).…”
Section: Resultssupporting
confidence: 93%
“…There is very limited data on occupational exposure to EMF at BCs. The findings of our study are consistent with other reported data from Poland [11], where the values ranging 0.4-9.6 V/m were found in workplac- es operating at VHF (87.5-108 MHz). Electromagnetic fields exposure in Polish BCs was slightly lower than that reported by Vangelova et al in the Bulgarian Broadcast Centers [5], where the equivalent time-weighted average was 2.12-3.9 V/m (vs. 0.54-2.74 V/m in this study).…”
Section: Resultssupporting
confidence: 93%
“…Additionally, the thickness of a material affects the shielding performance; thicker materials are required to shield the magnetic field component of EM radiation, while thinner materials are sufficient for the electrical field component of the radiation. [7] Shielding electromagnetic waves is of great importance, and consequently, many studies have been conducted in this field. The most desirable features in such studies are low density and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulation or numeric methods are used rather for the analysis purposes and exclude environment influence. The specificity of the electromagnetic field measurements methodology and exposure assessment for the purpose of occupational safety has been often discussed, e.g., by Aniołczyk et al [4] and Kubacki et al [5], particularly in the context of HF welders: by Aniołczyk et al [6], Bieńkowski and Zubrzak [7], and Bieńkowski et al [8]. The study of the electromagnetic field distribution is shown by Eriksson and Mild [9] and Conover et al [10], while the issue related to assessment of exposure to EMF from dielectric welders is presented by Conover et al [11].…”
Section: Introductionmentioning
confidence: 99%